Turkish phrase book & dictionary - Sekhavati, Zara (Berlitz Publishing, 2019)
Berlitz Phrasebook and Dictionary Turkish Compact, clear, and packed with key words and phrases to help conversation, this pocket-sized Turkish phrasebook and dictionary from Berlitz's trusted language experts (with free app) is a trusty travel companion, and all you need to make yourself understood - and to understand others - when you're out and about in Turkey. · With its emphasis on conversational usage, and up-to-date language on social media, leisure, business - and more - this is the only phrase book you'll need when exploring Turkey · Includes 3000-word bilingual dictionary · Visually appealing colour-coding system means you can find what you want, when you want, and fast · The simplified Berlitz pronunciation system will ensure you're clearly understood · Stunning colour photography enhances the expert content, and makes this series the most visually attractive phrase book on the market About Berlitz: Berlitz draws on years of travel and language expertise to bring you a wide range of travel and language products, including travel guides, maps, phrase books, language-learning courses, dictionaries and kids' language products.